Adoption and use of health information technology in physician practice organisations: systematic review - Rachel Police (Journal of Innovation in Health Informatics, 2010)
Background Health information technology (HIT) has the potential to improve clinical outcomes, increase health provider productivity and reduce healthcare costs. Over half of all patient care is delivered in physician practice organisations, yet adoption and utilisation of HIT in these groups lags behind inpatient facilities. Objective To better understand current utilisation rates along with benefits and barriers to HIT adoption in physician practice organisations. Methods Published literature on the adoption and use of HIT in physician practice organisations within the USA between 12 January 2004 and 12 January 2009 and indexed in MEDLINE and EMBASE was included in the systematic review. Grey literature was also searched. Studies related to the adoption and use of HIT in hospitals and community health centres were excluded. Results A total of 119 articles were eligible for inclusion in the review. Adoption rates across physician groups remain low, with between 9% and 29% of practices having implemented electronic medical records. HIT improves clinical outcomes, increases the use of vaccinations and improves medication adherence. Furthermore, HIT adoption leads to cost savings for physician groups, improves staff productivity and enriches patient_provider interactions. The largest barrier to HIT adoption in physician groups is the high initial and ongoing costs of electronic systems. Lack of sufficient training, a disorganised or non-receptive practice culture and technological problems such as inadequate connectivity appear to impede effective HIT use. Conclusions HIT has the potential to positively impact on physician practice organisations, although significant and diverse barriers block adoption. Research into these obstacles should be coupled with efforts to understand barriers to effective implementation after HIT adoption.